AlGaInP LASER EFFECTS ON NEUROPATHYC ULCERS HEALING ON LOWER EXTREMITIES IN CARRYING PATIENTS OF DIABETES MELLITUS. (Fiep Bulletin - online, 2014)
The objective of this study was to verify the AlGaInP laser effects on neuropathyc ulcers healing on lower extremities in carrying patients of diabetes mellitus. To take care of oneself a research of clinical character almost experimental, of the type intervention, carried in the physiotherapy Clinical School of the UESB, of which six patients participated with total of eight ulcers. It was found an average reduction of the ulcers with p was verified equal value the 0,018. It is concluded that the AlGaInP laser´s application, in dose of 4J/cm2, punctual and in the edges revealed efficient, promoting improvement in the cicatricial process.
Keywords: Diabetes Mellitus; cicatrization; laser; ulcers